The effects of ground surfaces – material, color & texture towards the adjacent thermal environment: a case study of plazas in Putrajaya, Malaysia - Abu Bakar, Aniza; Hj Mohd Ariffin, Noor Aziah (2012)
Urban heat island (UHI) is the terminology used to describe a condition whereby the temperature within an urban area or a city is often warmer than the outer suburbs and surrounding rural environments. Cities in Malaysia are also facing this environmental issue. Buildings and urban infrastructure such as road are among the component that made up the urban fabrics. The increment of air temperature among others is due to these components that apply materials that retain heat. The modification of land surfaces following urban development such as change of land use where natural environment is being replaced with hard surfaces also contributes to the UHI phenomena. Urban geometry, evaporative cooling source and wind pattern are other factors that contribute to the formation of urban heat island. This phenomenon negatively affects the social outdoor activities, health and economy. Therefore, this paper aims to study the impact of surface material in urban plazas on their microclimate by investigating plazas in Putrajaya, Malaysia. The investigation is divided into two subcategories where the first one is focusing on three different plazas: shaded, partially shaded and exposed plazas where these plazas are studied to compare and contrast on their landscape settings and surface temperature of various surface materials. The second sub-category is focusing on another two plazas – Dataran Wawasan (exposed plaza) and Dataran Rakyat (partially shaded plaza) that have similar orientation, dimension and physical site context. Environmental variables considered in this research are wind speed, solar radiation and cloud cover. This study aims to explore the influences and significance of certain types of pavement surfaces that vary in term of its material, color, and texture towards the surrounding thermal environment of the studied sites subsequently provide few recommendations through design initiatives that are feasible to mitigate the UHI effects in urban areas.